Kajian Hukum Pidana Terhadap Penetapan Tersangka Dengan Alat Bukti Yang Sudah Digunakan Dalam Perkara Orang Lain (Analisis Putusan Nomor 97/PID.PRAP/2017/PN.JKT.SEL) - Abroryan Nur (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
The regulation regarding the appointment of a person as a suspect based on evidence that has been used in other cases is not legally found. However, the determination of a suspect must be based on sufficient preliminary evidence, that is, with the minimum 2 (tools) of evidence as stipulated in Article 1 point 14 KUHAP Jo. Article 66 paragraph (1) and paragraph (2) of the National Police Regulation Number 12 of 2009. Criminal law review of the determination of a suspect with evidence that has been used in someone else's case (Analysis of Decision Number 97 / Pid. Prap / 2017 / PN.Jkt. Cell) is based on pretrial decision no. 97 / pid.prap / 2017 / pn.jkt.sel that with Judge Cepi Iskandar's consideration there would be the possibility of becoming a new jurisprudence. If a new jurisprudence is made, then in resolving a criminal case with inclusion such as corruption where the suspect's statement cannot later be used as the development of further investigations for other suspects.